The cult of Saint Thecla : a tradition of women's piety in late antiquity - Davis, Stephen J. (Oxford early Christian studies., 2001)
Thecla, a disciple of the apostle Paul, became perhaps the most celebrated female saint and 'martyr' among Christians in late antiquity. In the early church, Thecla's example was associated with the piety of women - in particular, with women's ministry and travel. Devotion to Saint Thecla quickly spread throughout the Mediterranean world: her image was painted on walls of tombs, stamped on clay flasks and oil lamps, engraved on bronze crosses and wooden combs, and even woven into textile curtains. Bringing together literary, artistic, and archaeological evidence, often for the first time, Stephen Davis here reconstructs the cult of Saint Thecla in Asia Minor and Egypt - the social practices, institutions, and artefacts that marked the lives of actual devotees. From this evidence the author shows how the cult of this female saint remained closely linked with communities of women as a source of empowerment and a cause of controversy.